PRAKTIK KEBERAGAMAAN PEREMPUAN PEKERJA SEKS DI SOSROWIJAYAN KULON YOGYAKARTA; TINJAUAN MAQASID SYARI'AH - Faiz Fikril Abror (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This study aims to describe the behavior of the women sex workersâ€™s religious practice in Sosrowijayan Kulon, Yogyakarta using the theory of maqa>sid syariah. During this education known as the city of Yogyakarta. However, it cannot be denied that the city now transformed as a tourism city. Lots of entertainment presented, one of which is known as the localization â€œPasar Kembangâ€ (sarkem). This study is a qualitative study of the field with the theory of maqa>sid syariah to reveal religious identity sex workers. As for the results that researchers have found is (1) in religion practice or Behavior aspects of worship they do going contention between Maqa>s}id al-Mukallaf and maqa>sid syariah. In this case on Hifz}u al-Di>n. Things that they believe to be the al-Hifzu In their version n in fact is a Maqa>s}id Mulghah are not permitted in Islam. Either way, however they are not allowed to undergo it. (2) in the aspects of factors that make them choose the profession of sex workers, when viewed from a glass eye maqa>sid syariah experience contradictions between Hifz}u al-Nafs with Hifz}u al-Nasl. In the end more won Hifz}u al-Nasl. Because basically the law adultery is haraam. So what they believe to be included in the category Maqa>s}id Mulghah.